Evaluating Scale Efficiency of Industry Clusters: a DEA Approach - Stichhauerova, Eva; Zizka, Miroslav; Lamr, Marian (Transformations In Business & Economics, 2026)
The paper deals with the impact of the existence of clusters on the efficiency of firms in terms of scale. The research subject is seven industries, six of which are manufacturing industries (automotive, engineering, furniture, nanotechnology, packaging and textile industries) and one service industry (IT). Technical and scale efficiencies were investigated in these industries from 2009 to 2021. The analysed firms were divided into two groups. The first group consists of members of the cluster organisation and companies operating in the same region as the cluster organisation. They may, therefore, share to some extent the positive externalities of the cluster organisation. The second group then represents other firms from more distant regions. The results show no positive impact of the existence of clusters on scale efficiency. Only in one industry - textile - a significant difference in the level of scale efficiency was found, but in reverse order. That is, non-clustered textile firms have achieved higher scale efficiency than clustered firms. Three industries (furniture, IT and packaging) are dominated by companies in conditions of increasing returns to scale. In the automotive industry, companies were on average close to optimal scale production around 2018-2019. However, the COVID-19 pandemic and subsequent sales problems in the industry marked a turning point for scale efficiency. In IT services, clustered companies in particular were close to optimal scale. In other industries, companies operating in a situation of declining returns to scale were significantly more prevalent.